Ze wspomnień mojego dziadka ("Być dobrym człowiekiem, reszta się nie liczy?") = From my grandfather`s memories - Hładkiewicz, Wiesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the everyday life of the inhabitants of the village of Nowosiołka Koropiecka. Many of them were impoverished nobility, free from serfdom. Their main occupation for livelihood was the cultivation of fertile land and cattle breeding. They dressed modestly and celebrated family holidays very solemnly. Everyday life was diversified with feasting and singing, they were very religious and attended church regularly. Their lives, work, troubles and joys are depicted in the above memoir.
Keywords: Kresy; Podole; Koropiec; Nowosiołka Koropiecka